p38α Mitogen-Activated Protein Kinase Is a Druggable Target in Pancreatic Adenocarcinoma - Yang, Ling; Sun, Xiaoting; Ye, Ying; Lu, Yongtian; Zuo, Ji; Liu, Wen; Elcock, Adrian; Zhu, Shun (Frontiers in Oncology, 2019)
p38 mitogen-activated protein kinases are signaling molecules with major involvement in cancer. A detailed mechanistic understanding of how p38 MAPK family members function is urgently warranted for cancer targeted therapy. The conformational dynamics of the most common member of p38 MAPK family, p38α, are crucial for its function but poorly understood. Here we found that, unlike in other cancer types, p38α is significantly activated in pancreatic adenocarcinoma samples, suggesting its potential for anti-pancreatic cancer therapy. Using a state of the art supercomputer, Anton, long-timescale (39 us) unbiased molecular dynamics simulations of p38α show that apo p38α has high structural flexibility in 6 regions, and reveal potential catalysis mechanism involving a “butterfly” motion. Moreover, in vitro studies show the low-selectivity of the current p38α inhibitors in both human and mouse pancreatic cancer cell lines, while computational solvent mapping identified 17 novel pockets for drug design. Taken together, our study reveals the conformational dynamics and potentially druggable pockets of p38α, which may potentiate p38α-targeting drug development and benefit pancreatic cancer patients.